Speech perception abilities of adult cochlear implant listeners with single-sided deafness vs. bilateral hearing loss. (4th July 2022) - Sladen, Douglas P.; Zeitler, Daniel M.
Abstract : Objectives: The purpose of this study was to compare the speech perception abilities in adult cochlear implant recipients implanted for bilateral sensorineural hearing loss (BSNHL) with those implanted for single-sided deafness (SSD). Design: A total of 12 adults with BSNHL and 12 adults with SSD participated. Each participant completed a battery of speech perception measures including monosyllabic words, sentences, and consonant recognition. Results: Cochlear implant users with BSNHL performed higher on word and sentence recognition. Consonant recognition scores showed higher performance for CI listeners with BSNHL for voicing and manner, but not for place or articulation. Conclusions: Results of this study suggest that adults with SSD may have lower speech perception abilities with their cochlear implant when compared to adults implanted for BSNHL.